Changes over treatment in total clinical symptom scores in patients with traumatic keratitis - V.M. Sakovych; T.O. Ostrikova (Ukrainian Society of Ophthalmologists, 2018)
Background: Since corneal tissue hypoxia develops in patients with traumatic keratitis, investigation of changes over treatment in clinical symptom scores in patients with traumatic keratitis undergoing adjunctive hyperbaric oxygenation (HBO) is of practical value. Purpose: To investigate changes over treatment in clinical symptom scores in patients with traumatic keratitis undergoing adjunctive HBO. Material and Methods: Sixty-nine patients (69 eyes; age, 18 years to 75 years) with traumatic keratitis were included in this study. Patients of the HBO group (33 eyes) received HBO therapy including 40-minute daily sessions in the OKA HBO chamber (operating in the 1.2 ATA mode) for 6 to 10 days as an adjunct in a comprehensive program of keratitis care. Changes over treatment in clinical symptom scores were investigated using the scale we developed. Results: By the end of treatment, in the HBO group, the total mean clinical symptom score was 39.4% lower, and mean scores related to corneal fluorescein staining, corneal edema, inflammatory conjunctival injection and inflammatory infiltration were 40%, 59.09%, 18.2%, and 40%, respectively, lower than in controls (p < 0.01). At the end of treatment, mean BCVA in the HBO group was 30.51% higher than in controls (p < 0.001). Conclusion: The use of adjunctive HBO contributed to substantial improvements in clinical symptom scores and BCVA in patients with traumatic keratitis.